Hubungan Sikap Pimpinan Dengan Kepuasan Kerja Pegawai Di Dinas Pendidikan Kabupaten Pasaman Barat - Anisa Pertiwi (Jurnal Bahana Manajemen Pendidikan, 2013)
This research aimed to describe the job satisfaction, attitude of the leadership and attitude of the leadership relationship with employee job satisfaction at Dinas Pendidikan Kabupaten Pasaman Barat. The population is 62 people and samples is employe 45 people. Large samples are determined based on Proportional Stratified Random Sampling. The research instrument was a questionnaire defferensial semantic models and Likert scale. Data analyzed by correlation technique Product Moment. The results is a pretty job satisfaction, attitude and a significant relationship between attitude of the leadership with employee satisfaction at Dinas Pendidikan Kabupaten Pasaman Barat. Kata kunci: sikap pimpinan; kepuasan kerja